ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2019 - Ida Indriyani Masruroh; Setyaningsih Sri Utami; Dorothea Ririn Indriastuti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
This research aims to obtain the effect of profitability, leverage, and company size on the disclosure of Corporate Social Responsibility on banking companies listed on the Indonesian stock exchange in 2015 - 2019. CSR disclosure can be seen on the sustainability report reported by company. Measurment of CSR Diclosure index with Global Reporting Initiative Generation 4 (GRI G4). This research uses a population of 43 banking companies listed on the Indonesia Stock Exchange in 2015 - 2019. The sample in this research 10 companies with sampling technique purposive sampling method. The analysis technique used in this study is the classic assumption test, multiple linear regression test, and hypothesis testing. The results of this research indicate that partially leverage has a significant effect while profitability and size companies do not significantly influence the disclosure of Corporate Social Responsibility on banking companies listed on the Indonesia Stock Exchange in 2015 - 2019.